PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP TINGKAT PROFITABILITASPADA KUD PRATAMA JAYA KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI (RIAU) - Anggraini, Ria; Ramayani,, Citra; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This study aims to analyze the influence of cash turnover , receivables turnover and inventory turnover to the level of profitability in KUD Pratama Jaya subdistrict singing Kuantan district Singingi ( Riau ) type of research is a quantitative approach , the processed secondary data obtained directly from KUD Pratama Jaya form of financial statements 2003 -20 012 . The analytical method used is multiple linear regression , F test and t test . Test results obtained by partial hypothesis , cash turnover significant effect on profitability ( 0.049 < Î± = 0.05 ) . Accounts receivable turnover has no significant effect on profitability ( 0.143 > Î± = 0.05 ) . Inventory turnover significant effect on profitability ( 0.044 < Î± = 0.05 ) . Testing hypotheses simultaneously , cash turnover , accounts receivable turnover , inventory turnover and significant effect on profitability ( 0.002 < Î± = 0.05 ) . and the results of this study showed that 89.5 % variabek profitability is affected by the independent variable , while the remaining 10.5 % is influenced by other variables that are not counted in this study